Energy availability and interstitial fluid glucose changes in elite male japanese triathletes during training camp: A case study - Hiromatsu, C.; Goto, K. (Nutrients, 2024)
This study explored the impact of varying energy availability (EA) on the 24-h interstitial fluid glucose concentration (IGC) in five elite male Japanese triathletes at a training camp. Measurements of IGC, energy and macronutrient intake, and exercise energy expenditure (EEE) through metabolic equivalents (METs) from training logs were conducted. Three subjects were evaluated over two 4-day periods, and two subjects over one 4-day period. Findings revealed significant correlations of daily mean nocturnal IGC with daily EA (r = 0.553, p = 0.001) and energy intake (EI) (r = 0.595, p < 0.001). However, no significant correlation was found between mean daily nocturnal IGC and EEE (r = -0.278, p = 0.124). Daytime IGC was =110 mg/dL for >50% of the time in all subjects, except on 1 day in one subject, and never fell <70 mg/dL. Therefore, daily EA may influence nocturnal IGC in elite male triathletes, although high daytime IGC levels were maintained without hypoglycemia.